Politeness in Kisangani Swahili - Nassenstein, Nico (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
Studies on Kiswahili in terms of speakers’ pragmatic strategies of politeness have so far only focused on standardized Kiswahili from the East African coast. However, apart from morphosyntactic contact-induced change, also pragmatic strategies among Kisangani-based Kiswahili speakers largely diverge from coastal speakers’ modes of interaction. Especially politeness patterns, as claimed in this paper with reference to speakers’ broad multilingual repertoires, are prone to pragmatic change, strongly influenced by politeness strategies usually associated with Lingala. Offering a first overview of the pragmatics of politeness in Kisangani Swahili, I primarily focus on face-threatening acts (FTA), third party face, concepts of shame and respect, self-censoring and also speakers’ ways of expressing criticism. Moreover, based on existing studies for ECS (East Coast Swahili), the pragmatic analysis of Kisangani Swahili includes a discussion of directives with specific reference to neighboring varieties such as Kivu Swahili, and also sheds light on the use of honorifics and terms of address in the language.